Sulcus subarachnoid hemorrhage is a common stroke subtype in patients with implanted left ventricular assist devices. (9th April 2015) - Sakaguchi, M.; Kitagawa, K.; Okazaki, S.; Yoshioka, D.; Sakata, Y.; Mochizuki, H.; Sawa, Y.; Yoshimine, T.
<x xml:space="preserve">Abstract</x> Background and purpose Stroke is one of the major complications observed in patients with an implanted left ventricular assist device (LVAD). The purpose of this study was to clarify the types and characteristics of acute stroke in patients after LVAD implantation by using brain computed tomography (CT) findings. Methods Between 2005 and 2012, 110 consecutive patients who underwent LVAD implantation were reviewed. The most commonly used device was the pulsatile extracorporeal LVAD. Amongst them, 49 patients suffered from acute stroke at least once with a total of 115 stroke events. The clinical categories, lesion sites, laboratory data and CT findings of each acute stroke event were analyzed. Results Cerebral infarction (35 patients, 72 events), cerebral hemorrhage (25 patients, 31 events) and subarachnoid hemorrhage (SAH) (23 patients, 33 events) were identified. A mean of 2.3 stroke events occurred per person. Of the 72 infarction events, multiple infarctions were observed in 29 events. Of the cerebral hemorrhage events (n = 31), almost all were subcortical lesions (n = 27) and none were observed in the basal ganglia. Of the 23 patients with SAH events (n = 33), SAH localized within a single sulcus, sulcus SAH, was observed in 25 events. Conclusions Computed tomography findings of acute stroke after implantation of an LVAD are characteristically multifocal cortical lesions, regardless of brain infarction and hemorrhage. Unexpectedly, sulcus SAH was a common stroke subtype in patients with implanted LVADs. Sulcus SAH should be carefully examined in patients after LVAD implantation, when they complain of non‐specific neurological complaints.